2022
DOI: 10.1038/s41467-022-30766-x
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the performance of single-atom catalysts via external electric field polarization

Abstract: Single-atom catalysts represent a unique catalytic system with high atomic utilization and tunable reaction pathway. Despite current successes in their optimization and tailoring through structural and synthetic innovations, there is a lack of dynamic modulation approach for the single-atom catalysis. Inspired by the electrostatic interaction within specific natural enzymes, here we show the performance of model single-atom catalysts anchored on two-dimensional atomic crystals can be systematically and efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 107 publications
1
52
0
Order By: Relevance
“…It further proved that the CN-F-catalyzed • OH generation was greatly enhanced under the electric field stimulation. All of these results confirmed that the TENG-enabled self-powered electric field can greatly improve the catalytic • OH production of CN-F, which may be attributed to the fact that the electric field promoted the charge transfer rate of the π-conjugated electrons in g-C 3 N 4 , leading to the enhancement of the π-conjugated electron leaving domains within its layers and the optimization of the mobility of the interlayer carriers, which in turn promotes catalysis …”
Section: Resultsmentioning
confidence: 99%
“…It further proved that the CN-F-catalyzed • OH generation was greatly enhanced under the electric field stimulation. All of these results confirmed that the TENG-enabled self-powered electric field can greatly improve the catalytic • OH production of CN-F, which may be attributed to the fact that the electric field promoted the charge transfer rate of the π-conjugated electrons in g-C 3 N 4 , leading to the enhancement of the π-conjugated electron leaving domains within its layers and the optimization of the mobility of the interlayer carriers, which in turn promotes catalysis …”
Section: Resultsmentioning
confidence: 99%
“…Finally, applying electromagnetic fields or controlled voltage may offer a promising strategy to tune the orbital configuration and spin state of the metal active sites. 90 Future studies are encouraged to explore these aspects, holding promise for exciting discoveries. ■ CHARACTERIZATION APPROACHES Established Methodologies.…”
Section: ■ Engineering Strategiesmentioning
confidence: 99%
“…external electric field, the reaction rate and selectivity of chemical reactions can be adjusted at will [18,28,29,59,61].…”
Section: Orléans Francementioning
confidence: 99%